SUCCESS FACTORS OF EQUITY CROWDFUNDING AND RURAL BANKS - Sumiyati, Sumiyati (Universitas Airlangga, 2025)
The campaign success factors of Equity Crowdfunding (ECF), such as the size of the project to be financed, profitability, liquidity, the amount of funding successfully funded by investors, the age of the company, and the number of targets achieved, influence company owners to choose bank financing or ECF. This research aims to determine whether ECF can replace the role of banks or complement it. The population of this study is made up of banks and ECF fintech institutions in Indonesia. The sample banks have at least one branch office in a region, while ECF institutions are ECFs that have an official Financial Services Authority (OJK) license. Hypotheses will be tested with logistic regression.The research results indicate that ECF can replace the role of banks, especially for start-up companies, but can also complement the role of banks, especially for MSMEs whose businesses have been running for a long time. This research is expected to provide a new perspective on the role of ECF and banks, especially for small and start-up companies, which are currently growing very rapidly and can support the national economy.